Pollution and City Size: Can Cities be too Small? - Rainald Borck; Takatoshi Tabuchi (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the optimal and equilibrium size of cities in a city system model with environmental pollution. Pollution is related to city size through the effect of population on production, commuting, and housing consumption. With symmetric cities, if pollution is local or per capita pollution increases with population, we find that equilibrium cities are too large. When pollution is global and per capita pollution declines with city size, however, equilibrium cities may be too small. With asymmetric cities, the largest cities are too large and the smallest too small when pollution is local or per capita pollution increases with population; when pollution is global and per capita pollution decreases with population, the largest cities are too small and the smallest too large. We also calibrate the model to US cities and find that the largest cities may be undersized by 3-4%.
Keywords: R12; Q54; 330; optimal city size distribution; agglomeration; pollution